Redefining flood hazard and addressing emerging risks in an era of extremes - Mohammad Shamsudduha (npj Natural Hazards)
Floods are intensifying globally, primarily due to climate change, with devastating impacts on lives and economies. Recent flash floods in Bangladesh, Central, and Western Europe highlight the ineffectiveness of current resilience strategies (e.g., drainage improvements) in mitigating extreme weather impacts. This commentary highlights the urgent need to shift focus towards flood risk reduction amid evolving flood hazard regimes while strengthening resilience through preparedness (e.g., dynamic warning systems) and adaptation strategies.